Roadmap on Electronic Structure Codes in the Exascale Era - Gavini, Vikram; Baroni, Stefano; Blum, Volker; Bowler, David R.; Buccheri, Alexander; Chelikowsky, James R.; Das, Sambit; Dawson, William; Delugas, Pietro; Dogan, Mehmet; Draxl, Claudia; Galli, Giulia; et al. (arXiv:2209.12747)
Electronic structure calculations have been instrumental in providing many important insights into a range of physical and chemical properties of various molecular and solid-state systems. Their importance to various fields, including materials science, chemical sciences, computational chemistry and device physics, is underscored by the large fraction of available public supercomputing resources devoted to these calculations. As we enter the exascale era, exciting new opportunities to increase simulation numbers, sizes, and accuracies present themselves. In order to realize these promises, the community of electronic structure software developers will however first have to tackle a number of challenges pertaining to the efficient use of new architectures that will rely heavily on massive parallelism and hardware accelerators. This roadmap provides a broad overview of the state-of-the-art in electronic structure calculations and of the various new directions being pursued by the community. It covers 14 electronic structure codes, presenting their current status, their development priorities over the next five years, and their plans towards tackling the challenges and leveraging the opportunities presented by the advent of exascale computing.

A High-Fidelity Flow Solver for Unstructured Meshes on Field-Programmable Gate Arrays: Design, Evaluation, and Future Challenges - Karp, Martin; Podobas, Artur; Kenter, Tobias; Jansson, Niclas; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (International Conference on High Performance Computing in Asia-Pacific Region)

Hermeneutik zwischen Logik und Ethik - Ficara, Elena (Ethik in der Hermeneutik – Hermeneutik in der Ethik)

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

CP2K on the road to exascale - Kühne, Thomas; Plessl, Christian; Schade, Robert; Schütt, Ole (arXiv:2205.14741)
The CP2K program package, which can be considered as the swiss army knife of atomistic simulations, is presented with a special emphasis on ab-initio molecular dynamics using the second-generation Car-Parrinello method. After outlining current and near-term development efforts with regards to massively parallel low-scaling post-Hartree-Fock and eigenvalue solvers, novel approaches on how we plan to take full advantage of future low-precision hardware architectures are introduced. Our focus here is on combining our submatrix method with the approximate computing paradigm to address the immanent exascale era.

Parallel quantum chemistry on noisy intermediate-scale quantum computers - Schade, Robert; Bauer, Carsten; Tamoev, Konstantin; Mazur, Lukas; Plessl, Christian; Kühne, Thomas (Phys. Rev. Research)
A parallel hybrid quantum-classical algorithm for the solution of the quantum-chemical ground-state energy problem on gate-based quantum computers is presented. This approach is based on the reduced density-matrix functional theory (RDMFT) formulation of the electronic structure problem. For that purpose, the density-matrix functional of the full system is decomposed into an indirectly coupled sum of density-matrix functionals for all its subsystems using the adaptive cluster approximation to RDMFT. The approximations involved in the decomposition and the adaptive cluster approximation itself can be systematically converged to the exact result. The solutions for the density-matrix functionals of the effective subsystems involves a constrained minimization over many-particle states that are approximated by parametrized trial states on the quantum computer similarly to the variational quantum eigensolver. The independence of the density-matrix functionals of the effective subsystems introduces a new level of parallelization and allows for the computational treatment of much larger molecules on a quantum computer with a given qubit count. In addition, for the proposed algorithm techniques are presented to reduce the qubit count, the number of quantum programs, as well as its depth. The evaluation of a density-matrix functional as the essential part of our approach is demonstrated for Hubbard-like systems on IBM quantum computers based on superconducting transmon qubits.

Roadmap on Electronic Structure Codes in the Exascale Era - Gavini, Vikram; Baroni, Stefano; Blum, Volker; Bowler, David R.; Buccheri, Alexander; Chelikowsky, James R.; Das, Sambit; Dawson, William; Delugas, Pietro; Dogan, Mehmet; Draxl, Claudia; Galli, Giulia; et al. (arXiv:2209.12747)
Electronic structure calculations have been instrumental in providing many important insights into a range of physical and chemical properties of various molecular and solid-state systems. Their importance to various fields, including materials science, chemical sciences, computational chemistry and device physics, is underscored by the large fraction of available public supercomputing resources devoted to these calculations. As we enter the exascale era, exciting new opportunities to increase simulation numbers, sizes, and accuracies present themselves. In order to realize these promises, the community of electronic structure software developers will however first have to tackle a number of challenges pertaining to the efficient use of new architectures that will rely heavily on massive parallelism and hardware accelerators. This roadmap provides a broad overview of the state-of-the-art in electronic structure calculations and of the various new directions being pursued by the community. It covers 14 electronic structure codes, presenting their current status, their development priorities over the next five years, and their plans towards tackling the challenges and leveraging the opportunities presented by the advent of exascale computing.

Towards electronic structure-based ab-initio molecular dynamics simulations with hundreds of millions of atoms - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Schütt, Ole; Lazzaro, Alfio; Pabst, Hans; Mohr, Stephan; Hutter, Jürg; Kühne, Thomas; Plessl, Christian (Parallel Computing)
Keywords: Artificial Intelligence; Computer Graphics and Computer-Aided Design; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science; Software

Effects of verbal negation on TVA’s capacity and weight parameters - Banh, Ngoc Chi; Scharlau, Ingrid (TeaP 2022 - Abstracts of the 64th Conference of Experimental Psychologists)

Folgen wiederholter Negation auf die Aufmerksamkeit - Banh, Ngoc Chi; Scharlau, Ingrid; Rohlfing, Katharina J. (52. Kongress der Deutschen Gesellschaft für Psychologie)

Gesundes Misstrauen gegenüber Erklärungen - Peters, Tobias Martin; Scharlau, Ingrid (52. Kongress der Deutschen Gesellschaft für Psychologie)

Unterrichtsbezogene Lehrpersonenkooperationen im Zeitalter der digitalen Transformation – Alles digital oder alles wie bisher? - Drossel, Kerstin; Heldt, M (MedienPädagogik)

Backward error analysis for variational discretisations of partial differential equations - McLachlan, Robert I; Offen, Christian (Journal of Geometric Mechanics)
In backward error analysis, an approximate solution to an equation is compared to the exact solution to a nearby ‘modified’ equation. In numerical ordinary differential equations, the two agree up to any power of the step size. If the differential equation has a geometric property then the modified equation may share it. In this way, known properties of differential equations can be applied to the approximation. But for partial differential equations, the known modified equations are of higher order, limiting applicability of the theory. Therefore, we study symmetric solutions of discretized partial differential equations that arise from a discrete variational principle. These symmetric solutions obey infinite-dimensional functional equations. We show that these equations admit second-order modified equations which are Hamiltonian and also possess first-order Lagrangians in modified coordinates. The modified equation and its associated structures are computed explicitly for the case of rotating travelling waves in the nonlinear wave equation.

Symplectic integration of learned Hamiltonian systems - Offen, Christian; Ober-Blöbaum, Sina (Chaos: An Interdisciplinary Journal of Nonlinear Science)
Hamiltonian systems are differential equations which describe systems in classical mechanics, plasma physics, and sampling problems. They exhibit many structural properties, such as a lack of attractors and the presence of conservation laws. To predict Hamiltonian dynamics based on discrete trajectory observations, incorporation of prior knowledge about Hamiltonian structure greatly improves predictions. This is typically done by learning the system's Hamiltonian and then integrating the Hamiltonian vector field with a symplectic integrator. For this, however, Hamiltonian data needs to be approximated based on the trajectory observations. Moreover, the numerical integrator introduces an additional discretisation error. In this paper, we show that an inverse modified Hamiltonian structure adapted to the geometric integrator can be learned directly from observations. A separate approximation step for the Hamiltonian data avoided. The inverse modified data compensates for the discretisation error such that the discretisation error is eliminated. The technique is developed for Gaussian Processes.

Bildungspolitische und einzelschulische Entwürfe von Bildung in Differenzverhältnissen. Mediatisierungstheoretische Analysen im Kontext qualitativ vergleichender Forschung - Hummrich, Merle; Dehmel, Lukas (Schulkulturen in Migrationsgesellschaften. Studien zu Differenzverhältnissen im deutsch-amerikanischen Vergleich)

Efficient Third-harmonic Generation Control with Ultrathin Dielectric Geometric-phase Metasurface - Liu, Bingyi; Huang, Lingling; Zentgraf, Thomas (Conference on Lasers and Electro-Optics)
Efficient third-harmonic generation control is theoretically studied. Dielectric nanostructures placed on the metallic substrate could offer effective geometric-phase modulation on third-harmonic signals by selecting proper structure rotational symmetry.

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Modeling-based learning about chemical phenomena in primary education - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (Fostering scientific citizenship in an uncertain world (Proceedings of ESERA 2021))

Analogien zur Förderung schülerseitigen Modellierens im Sachunterricht - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen)

Verstehensgrundlagen diagnostizieren - Diagnostisches Denken von drei Professionalisierungsgruppen - Dröse, Jennifer (Beiträge zum Mathematikunterricht)

Corporate Digital Responsibility Needed? Digitalization Meets Corporate Social Responsibility - Jakob, Eva Alexandra; Plaß, Sabrina (Academy of Management Proceedings)
Keywords: Microbiology

COVID-19 in German Competitive Sports: Protocol for a Prospective Multicenter Cohort Study (CoSmo-S) - Niess, Andreas Michael; Widmann, Manuel; Gaidai, Roman; Gölz, Christian Johannes; Schubert, Isabel; Castillo, Katty; Sachs, Jan Philipp; Bizjak, Daniel; Vollrath, Shirin; Wimbauer, Fritz; Vogel, Azin; Keller, Karsten; et al. (International Journal of Public Health)
Objective: It is unclear whether and to what extent COVID-19 infection poses health risks and a chronic impairment of performance in athletes. Identification of individual health risk is an important decision-making basis for managing the pandemic risk of infection with SARS-CoV-2 in sports and return to play (RTP). Methods: This study aims 1) to analyze the longitudinal rate of seroprevalence of SARS-CoV-2 in German athletes, 2) to assess health-related consequences in athletes infected with SARS-CoV-2, and 3) to reveal effects of the COVID-19 pandemic in general and of a cleared SARS-CoV-2 infection on exercise performance. CoSmo-S is a prospective observational multicenter study establishing two cohorts: 1) athletes diagnosed positive for COVID-19 (cohort 1) and 2) federal squad athletes who perform their annual sports medical preparticipation screening (cohort 2). Comprehensive diagnostics including physical examination, laboratory blood analyses and blood biobanking, resting and exercise electrocardiogram (ECG), echocardiography, spirometry and exercise testing added by questionnaires are conducted at baseline and follow-up. Results and Conclusion: We expect that the results obtained, will allow us to formulate recommendations regarding RTP on a more evidence-based level.
Keywords: Public Health; Environmental and Occupational Health; Health (social science)

Modeling and analysis of functional variance of complex technical systems - Menninger, Bastian; Wiechel, Dominik; Rackow, Sascha; Höpfner, Gregor; Oleff, Christian; Berroth, Joerg; Gräßler, Iris; Jacobs, Georg (DS 119: Proceedings of the 33rd Symposium Design for X (DFX2022))

Die Förderung von Reflexionskompetenz und Reflexion durch die angeleitete Bearbeitung eines weiterentwicklungsorientierten Online-Self-Assessments - Buhl, Heike M.; Sagolla, Nils; Bohndick, Carla (Lehrerbildung auf dem Prüfstand)

MultPAX: Keyphrase Extraction using Language Models and Knowledge Graphs - Zahera, Hamada Mohamed Abdelsamee; Vollmers, Daniel; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (ISWC 2022)
Keywords: colide dice eml4u ngonga raki sherif speaker vollmers zahera

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

Late-Career Unemployment and Cognitive Abilities - Freise, Diana; Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)
We study the effect of unemployment on cognitive abilities among individuals aged between 50 and 65 in Europe. To this end, we exploit plant closures and use flexible event-study estimations together with an experimentally elicited measure of fluid intelligence, namely word recall. We find that, within a time period of around eight years after the event of unemployment, cognitive abilities only deteriorate marginally — the effects are insignificant both in statistical and economic terms. We do, however, find significant effects of late-career unemployment on the likelihood to leave the labor force, and short-term effects on mental health problems such as depression and sleep problems.

Marginal College Wage Premium under Selection into Employment - Westphal, Matthias; Kamhöfer, Daniel A.; Schmitz, Hendrik (Economic Journal)

Labor market spillover effects of a compulsory schooling reform in Germany - Schiele, Valentin
Compulsory schooling reforms are often used to estimate monetary returns to education. Such reforms are unrelated to individual characteristics and preferences and thus arguably able to eliminate selection bias. However, as these reforms affect a large number of individuals in the relevant age groups, they might have spillover effects on individuals not directly affected by the reform. Such spillover effects constitute a problem for identification and estimation of returns to schooling. As they are difficult to address, they are mostly ignored in the empirical literature. I show that the introduction of the compulsory ninth grade in Germany led to a labor supply shock that might have increased wages and employment of individuals who were not directly subject to the reform and were assumed not to be affected in previous research. To investigate in this kinds of spillover effects, I exploit the staggered introduction of the compulsory ninth grade across German federal states in a difference-in-differences approach. Based on large scale register and survey data, I find no evidence for persistent spillover effects for men. For women, however, my results suggest that the labor supply shock resulting from the reform may have led to a persistent increase in employment and wages.
Keywords: Compulsory schooling; Education; Spillover effects; Cohort size; Wages; Employment

Can Tax Rate Changes Accelerate Investment under Entry and Exit Flexibility? – Insights from an Economic Experiment - Fahr, René; Janssen, Elmar; Sureth-Sloane, Caren (FinanzArchiv)
Keywords: Finance

Integrating Future Energy, Material and Production Scenarios in Life Cycle Engineering of Automotive Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Proceedings of the 17th Conference on Sustainable Development of Energy, Water and Environment Systems)

Individualisierung des ÖPNV - Integration technischer und sozialer Dimensionen nachhaltiger Mobilität - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fiabian (14. Wissenschaftsforum Mobilität)

Scholarship of Teaching and Learning – Eine forschungsgeleitete Fundierung und Weiterentwicklung hochschul(fach)didaktischen Handelns

Wirksamkeit von SoTL im Rahmen hochschuldidaktischer Weiterbildung auf die Weiterentwicklung der (Lehr-)Kompetenz. Das Vertiefungsmodul im Paderborner Zertifikatsprogramm - Vöing, Nerea (Hochschullehre erforschen)

Bestimmung von Stoffübergangskoeffizienten für Strukturpackungen basierend auf hydrodynamischen Analogien - Mapura Ramirez, Luz Alejandra; Kenig, Eugeny Y.

Menschenzentrierte Montageplanung und -steuerung durch fähigkeitsorientierte Aufgabenzuordnung - Gräßler, Iris; Roesmann, Daniel

Strategic emphasis on service-based business models during the corona crisis: Are customer solutions a curse or blessing for manufacturing firms? - Akalan, R.; Eggert, A.; Böhm, Eva (Journal of Service Management Research)

Digital technology usage as a driver of servitization paths in manufacturing industries - Eggert, A.; Harrmann, L.; Böhm, Eva (EMAC Annual Conference, Budapest, Hungary)

Should manufacturers publish online reviews in their own online shops? - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Budapest, Hungary)

Servitization in the manufacturing industry: Where do we stand? Where do we come from? - Akalan, R.; Böhm, Eva; Eggert, A. (Journal of Service Management Research)

Entwicklung handlungsnaher Prüfungsformate im Lehramtsstudium - Janzen, Thomas; Wotschel, Philipp; Vogelsang, Christoph (MoSAiK-Tagung 2022)

Das DigitELE Tutorial – Eine digitale Lernumgebung als asynchrones Angebot zur Unterstützung der synchronen Lehre in der Englischdidaktik - Janzen, Thomas; Gampert, Martha; Gabel, Stephan; Matz, Frauke; Reckermann, Julia (DiKuLe-Symposium 2022)

Between theory and practice: Rollenspielbasierte Simulationen als Prüfungsformat für handlungsnahe Feedbackkompetenzen angehender Englischlehrkräfte - Janzen, Thomas; Vogelsang, Christoph; Rumlich, Dominik (Professionstagung 2022)

Entwicklung eines Performanztests für das Lehramtsstudium im Fach Englisch: Feedback im Kompetenzbereich Schreiben - Janzen, Thomas (Woche des wissenschaftlichen Nachwuchses)

Entwicklung eines Performanztests für das Lehramtsstudium im Fach Englisch: Feedback im Kompetenzbereich Schreiben - Janzen, Thomas (GEBF-Nachwuchstagung 2022)

Weak Progressive Forward Simulation Is Necessary and Sufficient for Strong Observational Refinement - Dongol, Brijesh; Schellhorn, Gerhard; Wehrheim, Heike (33rd International Conference on Concurrency Theory, CONCUR 2022, September 12-16, 2022, Warsaw, Poland)

A Rollercoaster of Emotions – A Semantic Analysis of Fundraising Campaigns over the Course of the COVID-19 Pandemic - Grieger, Nicole; Seutter, Janina; Kundisch, Dennis (Proceedings of the 28th Americas Conference on Information Systems (AMCIS))

Peer-To-Peer Rentals, Regulatory Policies, And Hosts’ Cost Pass-Throughs - Müller, Michelle; Neumann, Jürgen; Kundisch, Dennis (Journal of Management Information Systems)

Репликация эффектов интерактивного решения задач спичечной алгебры - Спиридонов, Владимир; Ерофеева, Мария; Klowait, Nils; Ардисламов, Владлен; Морозов, Максим; Здилар, Стево (Психологические исследования)
Один из многообещающих вариантов внедрения моторной активности в процесс решения мыслительных задач был предложен в статье Weller и коллег. В ходе «интерактивного» условия эксперимента испытуемые могли взаимодействовать с реальными предметами, составлявшими проблемную ситуацию. Эта экспериментальная манипуляция привела к значимому увеличению успешности решения большинства использованных задач спичечной алгебры. С учетом того, что задачи различались по источникам сложности, трудно предложить один (или общий) вариант движений решателя, который мог бы объяснить одинаковое положительное влияние интерактивного условия на успешность решения задач разнойстепени сложности. Чтобы удостовериться в точности полученных результатов и оценить перспективность подобной экспериментальной манипуляции, мы провели концептуальную репликацию названного исследования в трех экспериментальных сериях, нацеленных: 1) напроверку эффектов интерактивного условия, 2) на расширенную репликацию тех же эффектов, поскольку она включала в себя экспериментальные условия, предполагающие разную степень моторной активности решателя, 3)на расширенную репликацию тех же эффектов, так как она содержала условия с максимально выраженной интерактивностью, благодаря использованию технологий виртуальной реальности. Кроме того, мы увеличили список зависимых переменных: помимо успешности решения было использовано количество эпистемических и прагматических действийрешателя. Увеличение количества первых может свидетельствовать о переносе части когнитивных функций на окружающую предметную среду. Ни в одном случае мы не смогли реплицировать результаты коллег. Хотя во второй серии эксперимента эпистемических действий было значимо больше, это никак не повлияло на успешность решения. Обсуждаются потенциал и проблемы интерактивного решения и его роль для изучения воплощенного познания.

Репликация эффектов интерактивного решения задач спичечной алгебры - Спиридонов, Владимир; Ерофеева, Мария; Кловайт, Нильс; Ардисламов, Владлен; Морозов, Максим; Здилар, Стево (Психологические исследования)
Один из многообещающих вариантов внедрения моторной активности в процесс решения мыслительных задач был предложен в статье Weller и коллег. В ходе «интерактивного» условия эксперимента испытуемые могли взаимодействовать с реальными предметами, составлявшими проблемную ситуацию. Эта экспериментальная манипуляция привела к значимому увеличению успешности решения большинства использованных задач спичечной алгебры. С учетом того, что задачи различались по источникам сложности, трудно предложить один (или общий) вариант движений решателя, который мог бы объяснить одинаковое положительное влияние интерактивного условия на успешность решения задач разнойстепени сложности. Чтобы удостовериться в точности полученных результатов и оценить перспективность подобной экспериментальной манипуляции, мы провели концептуальную репликацию названного исследования в трех экспериментальных сериях, нацеленных: 1) напроверку эффектов интерактивного условия, 2) на расширенную репликацию тех же эффектов, поскольку она включала в себя экспериментальные условия, предполагающие разную степень моторной активности решателя, 3)на расширенную репликацию тех же эффектов, так как она содержала условия с максимально выраженной интерактивностью, благодаря использованию технологий виртуальной реальности. Кроме того, мы увеличили список зависимых переменных: помимо успешности решения было использовано количество эпистемических и прагматических действийрешателя. Увеличение количества первых может свидетельствовать о переносе части когнитивных функций на окружающую предметную среду. Ни в одном случае мы не смогли реплицировать результаты коллег. Хотя во второй серии эксперимента эпистемических действий было значимо больше, это никак не повлияло на успешность решения. Обсуждаются потенциал и проблемы интерактивного решения и его роль для изучения воплощенного познания.